Human Resource Management Practices and Employee Satisfaction in Nepalese Commercial Banks - Bhatt , Padam Raj (Journal of Research in Education, 2025)
This study explores how HRM practices arrangement employee satisfaction in Nepalese commercial banks. It focuses on the real stuff that matters, things like how banks hire people, train them, evaluate their work, handle promotions, and set up pay and benefits. The researcher communicated with around 176 bank employees in Sudurpaschim province to find a clear picture and fill out a prearranged questionnaire. The study used a five-point Likert scale to keep matter steady. The researcher used correlation and some basic statics methods to analyze the data. The study found that promotions, performance evaluations, social benefits, and compensation improve employee satisfaction in a big way. Even recruitment and training have a noticeable positive effect. Bottom line, good HRM practices don’t just make people happier; they improve commitment, motivation, and assistance and make the whole business run better. The study comes to the conclusion that Nepalese commercial banks cannot increase employee satisfaction, productivity, or competitiveness without using HRM techniques. It delivers managers with helpful suggestions on how to recover HR regulations and establish a positive, encouraging work atmosphere.